Dissolution behavior of TiN in liquid cobalt. (November 2020) - Zhong, Ming; He, Yining; Pistorius, Petrus C.; Webler, Bryan A.
Abstract: A confocal scanning laser microscope (CSLM) with a hot stage was used to study the dissolution of TiN in liquid cobalt under different gas atmospheres. The dissolution of cubic carbonitrides in cobalt is a key step in the formation of the cobalt enriched zone (CEZ) during cemented carbide production. A model system of cobalt + TiN was used in this work and in-situ observations were made at 1500 °C and 1550 °C in 5%H2 -Ar and 5%H2 -N2 . Dissolution was observed in 5%H2 -Ar but not 5%H2 -N2 . At 1550 °C in 5%H2 -Ar, gas bubbles were observed in the liquid cobalt and rapid dissolution was observed. The dissolution rate of TiN was quantified at 1500 °C in 5%H2 -Ar. The rate-controlling step of TiN dissolution was hypothesized to be mass transfer of nitrogen in the liquid cobalt to the liquid/gas interface. This was tested by using the shrinking core model to calculate the diffusivity of nitrogen based on the measured dissolution rates. The diffusivity was between 6.4 × 10 −5  cm 2 /s and 5.3 × 10 −4  cm 2 /s, which was consistent with a previous study (approximately 1 × 10 −4  cm 2 /s). The findings of this work can be utilized in detailed models of CEZ formation during cemented carbide production. Highlights: TiN dissolution in liquid cobalt was clearly observed in 5%H2 -Ar, but not in 5%H2 -N2 . TiN dissolution rate in liquid cobalt at 1550 °C was larger than at 1500 °C. Bubbles were generated at 1550 °C in 5%H2 -Ar and TiN crystal growth was observed at 1550 °C in 5%H2 -N2 . The estimated diffusivity of nitrogen in liquid cobalt at 1500 °C was approximately 3 × 10 −4 cm 2 /s.